2013
DOI: 10.1016/j.cell.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

An Extracellular Interactome of Immunoglobulin and LRR Proteins Reveals Receptor-Ligand Networks

Abstract: Extracellular domains of cell-surface receptors and ligands mediate cell-cell communication, adhesion, and initiation of signaling events, but most existing protein-protein “interactome” datasets lack information for extracellular interactions. We probed interactions between receptor extracellular domains, focusing on the Immunoglobulin Superfamily (IgSF), Fibronectin type-III (FnIII) and Leucine-rich repeat (LRR) families of Drosophila, a set of 202 proteins, many of which are known to be important in neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
293
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(324 citation statements)
references
References 72 publications
9
293
2
Order By: Relevance
“…As previously noted, one subset of URs corresponds to the major Drosophila Hox gene clusters, and we observed ;10 additional URs containing Polycomb-rich chromatin. Interestingly, we found that URs are also enriched in a class of genes not previously associated with repressive chromatin domains; namely, genes encoding IgG superfamily (IgSF) proteins ( € Ozkan et al 2013). Among the four classes of IgSF proteins characterized by € Ozkan et al (2013), 13 of 14 Beat class, seven of eight Side class, five of 11 DIP class, and nine of 20 Dpr class IgSF genes are in UR regions (Table 1).…”
Section: Ur Zones Are Enriched In Immunoglobulin Superfamily Genes Anmentioning
confidence: 87%
See 2 more Smart Citations
“…As previously noted, one subset of URs corresponds to the major Drosophila Hox gene clusters, and we observed ;10 additional URs containing Polycomb-rich chromatin. Interestingly, we found that URs are also enriched in a class of genes not previously associated with repressive chromatin domains; namely, genes encoding IgG superfamily (IgSF) proteins ( € Ozkan et al 2013). Among the four classes of IgSF proteins characterized by € Ozkan et al (2013), 13 of 14 Beat class, seven of eight Side class, five of 11 DIP class, and nine of 20 Dpr class IgSF genes are in UR regions (Table 1).…”
Section: Ur Zones Are Enriched In Immunoglobulin Superfamily Genes Anmentioning
confidence: 87%
“…Interestingly, we found that URs are also enriched in a class of genes not previously associated with repressive chromatin domains; namely, genes encoding IgG superfamily (IgSF) proteins ( € Ozkan et al 2013). Among the four classes of IgSF proteins characterized by € Ozkan et al (2013), 13 of 14 Beat class, seven of eight Side class, five of 11 DIP class, and nine of 20 Dpr class IgSF genes are in UR regions (Table 1). Since UR regions constitute only 19% of euchromatin, finding 34 of 53 IgSF genes in UR regions is unlikely to occur by chance (P < 10 À13 ; binomial distribution).…”
Section: Ur Zones Are Enriched In Immunoglobulin Superfamily Genes Anmentioning
confidence: 87%
See 1 more Smart Citation
“…9c). These structural comparisons indicate that many protein-protein interactions mediated by the extracellular Ig and LRR domain 32 have evolved to serve divergent functions in the CNS through the specific binding of distinct partners.…”
Section: Minimal Domain Identification For Binding and Synaptogenesismentioning
confidence: 99%
“…In contrast to the extreme molecular diversity of Dscam1, Drosophila Dscam2 encodes two distinct protein isoforms; Dscam2A and Dscam2B that interact in an isoform-specific homophilic manner (Millard et al, 2007;Ozkan et al, 2013). Cell-specific isoform expression was also previously shown to be important for lamina neuron arborisation (Lah et al, 2014).…”
Section: Down Syndrome Cell Adhesion Moleculementioning
confidence: 99%